Trace mercury speciation in specific Antarctic soils - Zvěřina, O.; Červenka, R.; Šimůnek, J.; Coufalík, P. (Pavel); Kuta, J.; Komárek, J. (2015)
This work assessed seals' carcasses as source of mercury, methylmercury and a promotors of further mercury methylation.